2017
DOI: 10.3324/haematol.2017.180539
|View full text |Cite
|
Sign up to set email alerts
|

Amotosalen/UVA pathogen inactivation technology reduces platelet activability, induces apoptosis and accelerates clearance

Abstract: Amotosalen/UVA pathogen inactivation technology reduces platelet activability, induces apoptosis and accelerates clearanceWith interest we read the paper by Stivala et al., 1 recently published in Haematologica, evaluating the structural and functional consequences induced by Amotosalen/UVA treatment using the Intercept Blood System (IBS) on platelets from apheresis platelet concentrates (PCs) during storage. This study provides results of early diminished platelet function in IBS-treated PCs as compared to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The INTERCEPT technique also moderately increases platelet storage lesions, which may account for the reduced posttransfusion platelet recovery reported in some clinical trials, without altering the hemostatic clinical performance of the cells 12,13 . Some of these lesions nevertheless appear to be reversible, since we have shown that INTERCEPT‐treated platelets, once isolated from their storage medium by washing and resuspended in a physiological buffer, exhibit spontaneous activation and functional properties very similar to those of untreated platelets 14,15 . The storage medium is therefore an additional parameter susceptible to influence the development of storage lesions.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The INTERCEPT technique also moderately increases platelet storage lesions, which may account for the reduced posttransfusion platelet recovery reported in some clinical trials, without altering the hemostatic clinical performance of the cells 12,13 . Some of these lesions nevertheless appear to be reversible, since we have shown that INTERCEPT‐treated platelets, once isolated from their storage medium by washing and resuspended in a physiological buffer, exhibit spontaneous activation and functional properties very similar to those of untreated platelets 14,15 . The storage medium is therefore an additional parameter susceptible to influence the development of storage lesions.…”
Section: Introductionmentioning
confidence: 81%
“…12,13 Some of these lesions nevertheless appear to be reversible, since we have shown that INTERCEPT-treated platelets, once isolated from their storage medium by washing and resuspended in a physiological buffer, exhibit spontaneous activation and functional properties very similar to those of untreated platelets. 14,15 The storage medium is therefore an additional parameter susceptible to influence the development of storage lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, PC transfusion carries a greater risk of bacterial contamination, which can be life threatening especially in severely immuno-compromised patients ( 51 ). The introduction of Pathogen Reduction Technologies has abrogated much of the adverse effects associated with pathogen contamination of platelet products ( 52 , 53 ). Pre-storage leukoreduction proved to significantly reduce inflammatory reactions as well as viral infections ( 54 ).…”
Section: A Brief Overview Of Pc Transfusion Benefits and Complicationmentioning
confidence: 99%
“…Several studies have reported reduced platelet function upon Intercept treatment (19,21,(32)(33)(34). Intercept has been shown to induce activation of p38, diminish the level of CD42 (also known as GpIb, which, in its complex, allows platelet adhesion and platelet clogging) (35), and deregulate expression of the pro-survival gene Bcl-xl and anti-apoptotic genes (21). In addition, to modulate the platelet mRNA transcriptome (19), Intercept was reported to alter platelet characteristics (mean volume), activation level, and aggregation response to physiological agonists (21).…”
Section: Discussionmentioning
confidence: 99%